2019
DOI: 10.1016/j.combustflame.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Vaporization model for arsenic during single-particle coal combustion: Model development

Abstract: The kinetic parameters for chemical reactions associated with the vaporization of arsenic species are rarely reported due to the difficulties in obtaining suitably purified arsenic compounds as well as the issues associated with the extreme toxicity of many arsenic species. Here, we used a single-particle coal combustion model combined with a vaporization yield model of arsenic fitted by experimental data, which was used to determine the activation energy and frequency factor of the oxidation/decomposition rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Synthetic gas mixtures O 2 , CO 2 , and H 2 O were injected into the furnace at a constant flow rate of 2.67 L/min, which not only eliminate the influence of external diffusion, but also avoid any sample thermal agglomeration during the combustion . In terms of the test results, the heating rate of char was estimated to be in the range of 5 × 10 3 to 10 4 K/s, which is closer to the heating rate for practical combustion in contrast to the TGA method. A number of previous studies have demonstrated that the isothermal combustion system can be successfully used to study char combustion and pollutant release.…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic gas mixtures O 2 , CO 2 , and H 2 O were injected into the furnace at a constant flow rate of 2.67 L/min, which not only eliminate the influence of external diffusion, but also avoid any sample thermal agglomeration during the combustion . In terms of the test results, the heating rate of char was estimated to be in the range of 5 × 10 3 to 10 4 K/s, which is closer to the heating rate for practical combustion in contrast to the TGA method. A number of previous studies have demonstrated that the isothermal combustion system can be successfully used to study char combustion and pollutant release.…”
Section: Methodsmentioning
confidence: 99%